2006
DOI: 10.1007/s10787-006-1512-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the efficacy of rofecoxib in monoarticular arthritis induced by latex of Calotropis procera and Freund’s complete adjuvant

Abstract: The role of prostaglandins in Calotropis procera latex induced inflammation and hyperalgesia has been well established. The acute inflammation induced by the dried latex (DL) of this plant could be effectively ameliorated by standard anti-inflammatory drugs. In present study we have evaluated the efficacy of rofecoxib, a COX-2 inhibitor in monoarthritis induced by intra-articular injection of DL and compared it with that against Freund's Complete Adjuvant (FCA). DL and FCA were injected into the right ankle jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 23 publications
(26 reference statements)
1
24
0
Order By: Relevance
“…reduced post-mortem analysis of ankle circumference and reduced the number of animals showing resistance to joint flexion and extension. Kumar et al [33] reported that another COX-2 inhibitor, rofecoxib, reduced nociceptive scores in the dorsal flexion pain test and the compression test; Wilson et al [38] also reported that rofecoxib and etoricoxib reduced changes in joint diameter and weight bearing in this CFA model during days 13-17. Increases in paw volume and ankle diameter have also been reported to be reduced by systemic administration of a selective prostaglandin E receptor 4 agonist given 24 h and 4 weeks after model induction [62].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…reduced post-mortem analysis of ankle circumference and reduced the number of animals showing resistance to joint flexion and extension. Kumar et al [33] reported that another COX-2 inhibitor, rofecoxib, reduced nociceptive scores in the dorsal flexion pain test and the compression test; Wilson et al [38] also reported that rofecoxib and etoricoxib reduced changes in joint diameter and weight bearing in this CFA model during days 13-17. Increases in paw volume and ankle diameter have also been reported to be reduced by systemic administration of a selective prostaglandin E receptor 4 agonist given 24 h and 4 weeks after model induction [62].…”
Section: Discussionmentioning
confidence: 81%
“…Meloxicam is a potent antiinflammatory agent that is commonly prescribed to treat arthritic conditions [29,30]. Moreover, inhibition of COX-2 has beneficial effects on nociceptive scores in animal models of inflammatory joint disease [31][32][33]. However, most studies have examined only the effects of acute inhibition of COX-2 [32,33] and longer treatment regimens measured effects only during the early phase of model development and on a restricted number of functional readouts.…”
Section: Introductionmentioning
confidence: 99%
“…In oncology, for example, nude mice transplanted with human xenografts are routinely used to assess the in vivo efficacy of anti-tumor agents (12,13). In immunology, rodents with arthritis, induced by agents such as collagen or adjuvant, are also common (14)(15)(16). Compounds acting on the central nervous system are evaluated similarly in various behavioral animal models, with a focus on brain penetration and target (e.g., receptor) occupancy (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…At first day, 100 µL of CFA was injected into the paw of the right hind limb of each rat except the normal control (Kumar et al, 2006). For 15 days the rats were housed without treatment to maintain the full development of inflammatory arthritic condition.…”
Section: Induction Of Arthritismentioning
confidence: 99%